SURVEY OF SMARTPHONE APPLICATION USAGE FOR DIABETES MANAGEMENT IN TYPE-2 DIABETES MELLITUS PATIENTS IN RSUPN DR. CIPTO MANGUNKUSUMO JAKARTA - Muharram, Arief Purnama; Soewondo, Pradana; Tahapary, Dicky Levenus (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION The rapid development of smartphone technology nowadays has enabled a new way of diabetes self-empowerment through the smartphone application usage. This study is aimed to obtain an overview of how smartphone and smartphone applications are used for diabetes management among Type-2 Diabetes Mellitus (T2DM) patients in RSUPN Dr. Cipto Mangunkusumo Jakarta (RSCM), a tertiary care and a national referral hospital in Indonesia. METHODOLOGY This cross-sectional study was conducted in the Integrated Diabetic Clinic RSCM during the 2nd-to-3rd week of May 2019 by using a short questionnaire, of which assessed the level of smartphone ownership and smartphone application usage for diabetes management. RESULTS Thirty-one respondents participated in this study. The average age was 59 years-old and most of them were either retired (13/31, 41.9%) or not working (13/31, 41.9%). Only 11 respondents had a higher degree of education. While most of the respondents (18/31, 58.1%) had a basic monthly income <1 million IDR (60 USD), majority of respondents (27/31, 87.1%) had a smartphone, of which all of them were using Android. Only one respondent used it for diabetes management, while most of them used it only for standard communication purpose. This was due to the lack of information on available diabetes application. CONCLUSION The use of smartphone among T2DM patients in our tertiary care hospital was high despite their low socioeconomic status. However, the smartphone application usage for diabetes management was very low, necessitating the need of information dissemination related to the potential benefit of diabetes application to all T2DM patients.